(untitled) (Bangladesh Journal of Child Health, 2012)
Background: Congenital heart disease poses much morbidity and mortality to children. During the past one-decade there have been encouraging improvements in the care of patients with congenital heart disease (CHD) seen in Bangladesh. The aim of the study was to determine the demography, characteristics, surgical result and complications of the entire operated patient with CHD during last four year and five months in United Hospital and to find out the importance of well-coordinated paediatric cardiac team in reducing case fatality rate. Method: This is a retrospective study based on patients record. The records of 457 patients were reviewed. Data of all patients with CHD who were operated from November 2006 to March 2011 at United Hospital, Dhaka were analyzed in this study. Result: Proportion of cyanotic congenital heart disease was 25%, among them tetralogy of Fallot (TOF) constitutes maximum number. Acyanotic heart diseases were mostly shunt lesion where 60% were associated with different degrees of pulmonary hypertension. Varied types of surgical procedures were done for correction of different types of CHD. Post operative complications were found in 125 (27%) patients. Since 2008 after implementation of well-coordinated paediatric cardiac team outcome of surgical procedure were improved. Case fatality rate which was 16% in 2007 came down to 8.3 % in 2010. Conclusion: Spectrum of CHD in our set-up was varied in nature. Though we have an acceptable mortality rate further improvement will be achieved from multidisciplinary progresses through developing a good, well-coordinated pediatric cardiac team. DOI: http://dx.doi.org/10.3329/bjch.v36i2.13079 BANGLADESH J CHILD HEALTH 2012; VOL 36 (2) : 61-65